Pengaruh Manajemen Laba, Ukuran Perusahaan, Corporate Social Responsibility Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bei Tahun 2018-2020) - Dwi Maya Anggraeni; Dwi Ermayanti Susilo (Forum Kerjasama Pendidikan Tinggi, 2022)
The main goal of every company is to optimize the company's profit as well as the wealth of its shareholders. Companies with high firm value will maximize the welfare of their shareholders, as a result, investors will be interested in investing in similar companies. There are several factors that can affect the value of the company which includes earnings management, firm size and corporate social responsibility. The purpose of this study was to determine the effect of earnings management, firm size, corporate social responsibility on firm value. The approach in this study uses a quantitative method approach. The population in this study are all companies in the mining sector listed on the Indonesia Stock Exchange in 2018-2020 totaling 48 companies. By applying the purposive sampling technique for sampling, 17 companies were obtained for 3 years, so the number of samples was 51. The data quality test uses the classical assumption test and the analysis technique uses multiple linear regression analysis. The results of this study indicate that earnings management has no significant effect on firm value, firm size has a positive and significant effect on firm value, and corporate social responsibility has no significant effect on firm value.